Mass Culture and Television: Quiz and Game Shows on TV Channels of Turkey, Lost Cultural Identities - Koncavar, Ayse (Mediterranean Journal of Social Sciences, 2012)
In the latest years, the number of quiz and game shows aired on Turkish TV channels has increased significantly. Theseshows serve as a shelter where people can escape from the disturbing pressure of their daily realities. The values and structures ofthese programs derive from certain facets of the capitalist ideology and feed it, encouraging the greed and the competitive individualinherent in capitalism. People participating in certain game shows are scored according to what they know. The capital of the game showis the knowledge which functions in the same way as money. Here, knowledge is like the capital of the manufacturing process. It is not tothe benefit of the society but solely to the person participating in the quiz show. In addition to this, whatâ€™s actually valuable and importantin the game shows is the way knowledge is used, not the knowledge itself. The contestants are from low social and economic levels. Inthe same manner, the viewers at the studio directed to applause constantly. On the other hand, the viewers in front of the TV forget thebarbarity and the resentments of day to day life by spending their time in front of an empty and unnecessary game show. What canthese people acting as spectators do instead? For instance, as citizens, they may prefer to watch other TV programs by which they mayachieve greater consciousness of their rights and responsibilities. This way our hopes, culture and identity bygone in this â€˜happy idiotsâ€society. The understanding resulting from such polarity causes issues to be taken out of the context of social and historical complexitiesand be profiled simplistically. Quiz shows, which are examples of mass culture, are also tools for ideological canalization andexploitation. These programs confirm the faith of the masses in the system and integrate them into it. Attempting to study the quiz showand game show such as â€œWho Wants to be a Millionaire ?" or â€œWill You Marry Me ?â€ with a theoretical approach as well as an empiricalmethod, taking the idea that such shows aired on Turkish TV channels are a tool of cultural imperialism and that they serve the settlingdown of the consumer society.